Determination of piglets' rectal temperature and respiratory rate through skin surface temperature under climatic chamber conditions - Mostaço, Gustavo M.; Miranda, Késia O. Da S.; Condotta, Isabella C.F. Da S.; Salgado, Douglas D'alessandro [UNESP] (FapUNIFESP (SciELO), 2015)
In animal farming, an automatic and precise control of environmental conditions needs information from variables derived from the animals themselves, i.e. they act as biosensors. Rectal temperature (RT) and respiratory rate (RR) are good indicators of thermoregulation in pigs. Since there is a growing concern on animal welfare, the search for alternatives to measure RT has become even more necessary. This research aimed to identify the most adequate body surface areas, on nursery-phase pigs, to take temperature measurements that best represent the correlation of RT and RR. The main experiment was carried out in a climate chamber with five 30-day-old littermate female Landrace x Large White piglets. Temperature conditions inside chamber were varied from 14 °C up to 35.5 °C. The measurements were taken each 30 minutes, over six different skin regions, using a temperature data logger Thermochron iButton® - DS1921G (Tb) and an infrared thermometer (Ti). As shown by the results, the tympanic region is the best one for RT and RR monitoring using an infrared thermometer (TiF). In contrast, when using temperature sensors, the ear (TbE) is preferred to be used for RT predictions and the loin region (TbC) for RR.
Keywords: Animal welfare; Environmental control for swine; Physiological modelling; Precision livestock farming; Temperature sensors; Thermal control